An Analysis of EFL Learners’ Integrative and Instrumental Motivation Factor at English Language Education Undiksha - Mahendra, Made Surya; Dewi, Ni Luh Putu Eka Sulistia; Utami , Ida Ayu Made Istri (STKIP AGAMA HINDU SINGARAJA, 2020)
This study aimed (1) to analyze motivation’s factor that affects English Language Education Students in achieving learning English both in instrumental and integrative motivation; (2) to analyze the major factor of motivation that affect students; and (3) to analyze how the major factor of motivation influence the students in achieving their goal in learning English. The survey was employed as a method of data collection through questionnaires and interviews. Both instruments consisted of instrumental and integrative motivation, which each dimension involves three factors of motivation. The results showed that English Language Education students were affected by six motivation factors. Those are academic, social, economic, attitude toward learning the target language, attitude toward the target language community, and desire to learn the target language. Among those motivation factors, the academic and attitude toward learning the target language were the major factor that affects students in achieving their goal in language learning.